Rendimiento de biomasa verde de achicoria (Cichorium intybus L.) sometido a dos sistemas de siembra y tres tipos de abonos orgánicos, en el Sector Chabayan, Cantón Espejo, Provincia del Carchi - Montalvo Terán, Brenda Elizabeth (2018)
VII. SUMMARY The investigation was carried out in the sector Chabayan, 27 of September parroquia, Espejo canton, province of the Carchi, with the purpose of evaluating the yield of the forage chicory (Cichorium intybus L.), under two systems of sowing in furrows and to the volley, submitted to the application of three types of organic fertilizers. The applied foliar fertilizers were: biol, fruit tea and seaweed extract in a solution 20 cc/1 lt. of water, that was applied to the foliage by spraying at 45, 90 and 135 days after sowing. In the study, an experimental design of completely random blocks with factorial arrangement (A x B + 2) was used, with three treatments and three repetitions. The variables evaluated were: days to germination, height of plant, number of leaves, days to harvest, weight of foliage per square meter, yield of foliage per plot and yield of foliage per hectare. The mean comparison of the variables was performed with the Tukey test at 5% statistical probability. The results obtained 170 days after sowing show that the highest yield of foliage is obtained under the furrow sowing system, at a planting spacing of 20 cm between plants and 40 cm between rows; and under foliar application of fruit tea with a dose of 20 cc of solution / l of water, reaching a yield of 151.30 kg / ha for a single cut. The economic analysis showed no economic benefit for any treatment.